Laddat för elektrifiering - Svensson, Hanna; Öhrlund, Isak (2020)
Sweden is facing the challenge of reducing greenhouse gas emissions from the transport sector and uses the electrification of the vehicle fleet as the main strategy. Since greenhouse gas emissions are a result of market failure, interventions from third parties, such as the state, are necessitated for the market to remedy the problem. For this reason, the Swedish government has commissioned the Swedish Environmental Protection Agency (EPA) to subsidize measures that contribute to limiting emissions. The Climate Leap provides support for public charging stations with the aim of accelerating the transition towards an electrified vehicle fleet. A model for panel data with fixed effects is used in order to ascertain whether the support has had an impact and estimates the effect of the public charging stations on the new registration of rechargeable cars. The EPA has calculated the climate benefit of charging stations by estimating actual use. In this paper, an alternative estimation of climate benefit is established, wherein the effect of charging stations on new car sales is used instead to estimate the climate benefit. It is evident that the public charging stations supported by the Climate Leap have a significant impact on new car sales of rechargeable cars at both a national and regional level, excluding Northern Sweden. The climate benefit was found to be higher everywhere, except in the Northern region, compared to the model provided by the EPA. This may show that the climate benefit of public charging stations has so far been underestimated.